Propuesta de mejora para el control de adiciones en la fabricación de cemento en la planta argos zona franca (2021)
Cement is one of the most used industrial products worldwide since its invention in 1845 to the present day. This research focuses on solving the problem inside of the Argos Company located in the Cartagena Free Zone, in increasing the volume of clinker discharge from the silo to the conveyor belt, in addition to improving the characteristics of the cement with certain additives. The main objective is to carry out a mechanical design of a restrictor blade, which allows improving the cement manufacturing process and its quality to reduce costs. In the collection and analysis of the information during the application of the methodology, were used mechanical studies, statistical data, and the use of design software such as SolidWorks, fusion360, Auto Cad y Excel.